2014
DOI: 10.1371/journal.pone.0109510
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Influenza A Virus Matrix Protein M1: Variations on a Theme

Abstract: Matrix protein 1 (M1) of the influenza A virus plays multiple roles in virion assembly and infection. Interest in the pH dependence of M1's multiple functions led us to study the effect of subtle pH changes on M1 structure, resulting in the elucidation of a unique low-pH crystal structure of the N1-165-domain of A/WSN/33 (H1N1) M1 that has never been reported. Although the 2.2 Å crystal structure of M1 N-terminus shows a dimer with the two monomers interacting in a face-to-face fashion at low pH as observed ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 39 publications
5
54
0
4
Order By: Relevance
“…The repulsion between the monomers at pH 5 possibly drives the conformational change in the protein molecule, changing the interacting surface between M1 monomers (16) and explaining the lower surface coverage and the completely differently layered structure of M1 matrix protein under acidic conditions (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The repulsion between the monomers at pH 5 possibly drives the conformational change in the protein molecule, changing the interacting surface between M1 monomers (16) and explaining the lower surface coverage and the completely differently layered structure of M1 matrix protein under acidic conditions (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
“…Existing X-ray structures of M1 (14)(15)(16) show that the N-terminal part of M1 forms a dimer. There are small differences at pH 7 and pH 4 within a single protein monomer but completely different interactions between monomers in a dimer (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The M1 monomer (252 amino acid) is 60 Å long (40), carrying two globular regions-the N-terminal (1-164) and C-terminal (165-252)-linked by a proteasesensitive loop. Crystallographic studies have revealed that the M1 protein is composed of nine a-helices (H1-H9).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the influenza A virus M1 has been studied extensively by several research groups, but so far only structures of the N-terminal fragment are available (14)(15)(16)(17). Whereas the M1 N domain was found to adopt essentially the same fold in all four reported structures, solution pH appeared to have some effects on its intermolecular interaction, with dimers observed at acidic pH (14) and monomers at neutral pH (15).…”
mentioning
confidence: 97%